Analisis Konten Visual Pada Akun Instagram New Normal Burger Bar Ditinjau Dari Teori Retorika - Danis Suryadi; Jupriani Jupriani (Pusat Riset dan Inovasi Nasional, 2023)
Visual content is currently being loved by business activists to compete in introducing their business to customers. This has motivated one of the restaurant businesses, namely New Normal Burgerbar, in the city of Padang to make promotional efforts through their Instagram social media in order to attract customers. This proves that visual content is crucial in its application as an information medium. In this regard, a descriptive qualitative research was conducted to analyze how the role of rhetoric (ethos, pathos, and logos) in achieving interesting visual content results can be conveyed effectively.